Predicting Short‐term Risk of Arrhythmia among Patients With Syncope: The Canadian Syncope Arrhythmia Risk Score. (12th October 2017) - Thiruganasambandamoorthy, Venkatesh; Stiell, Ian G.; Sivilotti, Marco L. A.; Rowe, Brian H.; Mukarram, Muhammad; Arcot, Kirtana; Kwong, Kenneth; McRae, Andrew D.; Wells, George A.; Taljaard, Monica
Abstract: Background: Syncope can be caused by serious occult arrhythmias not evident during initial emergency department (ED) evaluation. We sought to develop a risk tool for predicting 30‐day arrhythmia or death after ED disposition. Methods: We conducted a multicenter prospective cohort study at six tertiary care EDs and included adults (≥16 years) with syncope. We collected standardized variables from clinical evaluation and investigations including electrocardiogram and troponin at index presentation. Adjudicated outcomes included death or arrhythmias including procedural interventions for arrhythmia within 30 days. We used multivariable logistic regression to derive the prediction model and bootstrapping for interval validation to estimate shrinkage and optimism. Results: A total of 5, 010 patients (mean ± SD age = 53.4 ± 23.0 years, 54.8% females, and 9.5% hospitalized) were enrolled with 106 (2.1%) patients suffering 30‐day arrhythmia/death after ED disposition. We examined 39 variables and eight were included in the final model: lack of vasovagal predisposition, heart disease, any ED systolic blood pressure < 90 or > 180 mm Hg, troponin (>99th percentile), QRS duration > 130 msec, QTc interval > 480 msec, and ED diagnosis of cardiac/vasovagal syncope (optimism corrected C‐statistic 0.90 [95% CI = 0.87–0.93]; Hosmer‐Lemeshow p = 0.08). The Canadian Syncope Arrhythmia Risk Score had a risk ranging from 0.2% to 74.5% for scores of –2 to 8. At a threshold score of ≥0, the sensitivity was 97.1% (95% CI = 91.6%–99.4%) and specificity was 53.4% (95% CI = 52.0%–54.9%). Conclusions: The Canadian Syncope Arrhythmia Risk Score can improve patient safety by identification of those at risk for arrhythmias and aid in acute management decisions. Once validated, the score can identify low‐risk patients who will require no further investigations.